PERANCANGAN CULTURE CRAFT CENTER SENI BUDAYA TRADISI MALUKU – TIFA SEBAGAI UPAYA PELESTARIAN SENI BUDAYA TRADISI INDONESIA - David Magetanapuang; Niken Savitri Anggraeni; Achmad Mucharam (Commed : Jurnal Komunikasi dan Media, 2022)
Art can be interpreted as a creation made by humans that has an element of beauty. Art is able to evoke one's emotions and feelings. Culture itself is a form of life that develops together in a group of people in a way that is passed down from generation to generation. Cultural arts become the most selling point that can use as a valuable foreign exchange resource for the country. Currently, foreign tourists prefer to enjoy tourist destinations that have a traditional feel. Meanwhile, Indonesian youth today still lack love for traditional arts and culture in Indonesia. Some even don't know it at all, because currently, schools in Indonesia, especially internationally, are more likely to introduce modern and digital cultural arts. It's sad when one day imagining this Indonesian traditional culture will be disappears